Volatility Connectedness on the Central European Forex Markets - Peter Albrecht; Evžen Kočenda (Center for Economic Studies and ifo Institute (CESifo), 2023)
We provide a comprehensive assessment of volatility connectedness between the currencies of Central European (CE) countries using high-frequency data from 2009 to 2022. We assess asymmetries in connectedness (not investigated for CE currencies before) and document domination of the negative volatility, especially during periods of economic distress. We further bring the first statistical evidence based on a formal bootstrap-after-bootstrap procedure of Greenwood-Nimmo et al. (2023) that increases in connectedness are linked with systematic events, and identify the impact of specific domestic and global shocks. We find that for eight out of eight endogenously selected global events, there was an increase in connectedness within a maximum of one business month from the event's occurrence. Finally, we show that the connectedness is linked with its potential drivers: uncertainty, liquidity, and economic activity whose impacts differ substantially. Our results are robust with respect to a volatility measure and provide direct policy implications for portfolio composition and hedging.
Keywords: C58; F31; F65; G01; G15; 330; volatility connectedness; Central European currencies; asymmetries in volatility connectedness; bootstrap-after-bootstrap procedure; portfolio composition and hedging